Evaluating the Effectiveness of MOOC-Based Learning for Enhancing Civil Servant Competence: A Case Study in Karanganyar Regency - Rahmawati Sururama; Kurnia Yuniasari (STAI Hubbulwathan Duri, 2024)
Education is crucial for enhancing the competencies of State Civil Apparatus (ASN) as public servants tasked with delivering quality services. To support this, the Indonesian government introduced a Massive Open Online Course (MOOC) program as an innovative approach to professional development. Karanganyar Regency was selected as the pilot region for MOOC implementation, given its readiness in digital infrastructure and its role as a model for other regions. This research aims to assess the effectiveness of the MOOC program in improving ASN competencies and to identify challenges to its successful implementation. Using a descriptive qualitative method with an inductive approach, the study collected data through observations, interviews with key stakeholders, and documentation analysis. Participants included ASNs enrolled in the MOOC program, program facilitators, and local government officials. Data analysis was conducted through reduction, presentation, and conclusion-drawing techniques. The findings indicate that the MOOC program significantly enhanced competencies such as digital proficiency, task management, and technical knowledge among ASNs. However, challenges were identified, including low quota fulfillment, suboptimal graduation rates, limited leadership control, and inadequate digital literacy among older participants. These barriers were compounded by inconsistent dissemination of information and limited participant engagement. Addressing these obstacles is vital to improving future MOOC implementations. Recommendations include enhanced leadership involvement, targeted training to improve digital literacy, and more effective communication strategies. The experience of Karanganyar Regency underscores the potential of MOOCs as a transformative tool for civil servant education, provided implementation challenges are systematically addressed.